A Tale of Two Farms : Agricultural support in India and Thailand - Maria C.S. Morales (2014)
For agricultural subsidies to be efficient in improving farmers’ incomes and eradicating hunger, holistic policy intervention is required. Complementary policies such as increased access to credit and information and improved farm infrastructure are essential in realising the objectives of such programs.